2011
DOI: 10.1044/1092-4388(2010/09-0255)
|View full text |Cite
|
Sign up to set email alerts
|

Examining Continuity of Early Expressive Vocabulary Development: The Generation R Study

Abstract: As the "Papers in Press" version of the manuscript, it has not yet undergone copyediting, proofreading, or other quality controls associated with final published articles. As the publisher and copyright holder, the American Speech-Language-Hearing Association (ASHA) disclaims any liability resulting from use of inaccurate or misleading data or information contained herein. Further, the authors have disclosed that permission has been obtained for use of any copyrighted material and that, if applicable, conflict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
136
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(159 citation statements)
references
References 34 publications
(49 reference statements)
18
136
2
3
Order By: Relevance
“…At a group level, all these factors seem to predict poor language outcome to some extent, but results are inconsistent and predictive value of outcome in individual cases is still too inaccurate to provide clinicians with a reliable guide in deciding which LTs should receive early language intervention Henrichs et al, 2011;Rice, Taylor, & Zubrick, 2008;Westerlund et al, 2006). The more reliable risk factors appear to be a delay in language comprehension (Bishop et al, 2012;Ellis Weismer, 2007;Henrichs et al, 2011;Silva, 1980;Thal, Tobias, & Morrison, 1991;Zambrana et al, 2014), a family history of language and literacy difficulties Lyytinen, Eklund, & Lyytinen, 2005;Reilly et al, 2010;Rice, 2012;Zambrana et al, 2014;Zubrick et al, 2007) and male gender (Henrichs et al, 2011;Horwitz et al, 2003;Reilly et al, 2010;Zambrana et al, 2014;Zubrick et al, 2007). It also seems to be generally accepted that the more risk factors are present, the higher the risk for persistent language deficits and the greater the need for clinical intervention (Desmarais et al, 2008;Ellis & Thal, 2008;Hawa & Spanoudis, 2014;Henrichs et al, 2011;Olswang et al, 1998;Paul & Roth, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…At a group level, all these factors seem to predict poor language outcome to some extent, but results are inconsistent and predictive value of outcome in individual cases is still too inaccurate to provide clinicians with a reliable guide in deciding which LTs should receive early language intervention Henrichs et al, 2011;Rice, Taylor, & Zubrick, 2008;Westerlund et al, 2006). The more reliable risk factors appear to be a delay in language comprehension (Bishop et al, 2012;Ellis Weismer, 2007;Henrichs et al, 2011;Silva, 1980;Thal, Tobias, & Morrison, 1991;Zambrana et al, 2014), a family history of language and literacy difficulties Lyytinen, Eklund, & Lyytinen, 2005;Reilly et al, 2010;Rice, 2012;Zambrana et al, 2014;Zubrick et al, 2007) and male gender (Henrichs et al, 2011;Horwitz et al, 2003;Reilly et al, 2010;Zambrana et al, 2014;Zubrick et al, 2007). It also seems to be generally accepted that the more risk factors are present, the higher the risk for persistent language deficits and the greater the need for clinical intervention (Desmarais et al, 2008;Ellis & Thal, 2008;Hawa & Spanoudis, 2014;Henrichs et al, 2011;Olswang et al, 1998;Paul & Roth, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, much research has focused on detecting predictors of different language trajectories in young children with late language emergence. This has shown that prediction of language outcome is poor if reliance is only placed on expressive language measures, especially when using early parent-report measures of language development Feldman et al, 2005;Henrichs et al, 2011;Westerlund et al, 2006). There is a need for multifactorial predictive risk models that include a wide range of verbal and nonverbal factors (Desmarais et al, 2008;Ellis & Thal, 2008;Hawa & Spanoudis, 2014;Olswang, Rodriguez, & Timler, 1998;Paul & Roth, 2011;Zambrana, Pons, Eadie, & Ystrom, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Andersson et al (2011) investigated gender differences in speech production for Swedish children aged between 18 to 24 months, and found that girls had higher mean scores than boys at 21 and 24 months, but not 18 months. In contrast to the above studies, two studies demonstrated non-significant gender effect in vocabulary acquisition (Heinrichs et al 2010, Hyde & Linn 1988. Hyde and Linn (1988) conducted a meta-analysis of over 170 studies on verbal ability, including vocabulary, and found no gender gap; or that the gender gap narrows and disappears all together in vocabulary acquisition for participants aged 3 to 21 years old.…”
Section: Gender and Vocabulary Learningmentioning
confidence: 99%
“…Hyde and Linn (1988) conducted a meta-analysis of over 170 studies on verbal ability, including vocabulary, and found no gender gap; or that the gender gap narrows and disappears all together in vocabulary acquisition for participants aged 3 to 21 years old. Based on the reports from mothers of 3759 children who completed the MacArthur Communicative Development Inventory at 18 months and the Language Development Survey at 30 months, Heinrichs et al (2010) found at both 18 and 30 months, that boys had a higher tendency to be delayed in expressive vocabulary skills than girls. However, the gender difference contribution to the overall variance was small.…”
Section: Gender and Vocabulary Learningmentioning
confidence: 99%